The Association of Surrogate Decision Makers’ Religious and Spiritual Beliefs with End of Life Decisions - Torke, Alexia M (J Pain Symptom Manage, 2019)
CONTEXT: Although religion and spirituality are important to surrogate decision makers, little is known about the role of religion in decision making regarding life sustaining treatments. OBJECTIVES: To determine the relationships between dimensions of religion and spirituality and medical treatment decisions made by surrogates. METHODS: This prospective, observational study enrolled patient/surrogate dyads from three hospitals in one metropolitan area. Eligible patients were 65 years or older and admitted to the medicine or medical intensive care services. Baseline surveys between hospital days 2-10 assessed seven dimensions of religion and spirituality. Chart reviews of the electronic medical record and regional health information exchange 6 months after enrollment identified the use of life sustaining treatments and hospice for patients who died. RESULTS: There were 291 patient/surrogate dyads. When adjusting for other religious dimensions, demographic, and illness factors, only surrogates’ belief in miracles was significantly associated with a lower surrogate preference for DNR status (Adjusted odds Ratio (aOR) 0.39, 95% confidence interval (CI) 0.19, 0.78). Among patients who died, higher surrogate intrinsic religiosity was associated with lower patient receipt of life-sustaining treatments within the last 30 days (aOR 0.66, CI 0.45, 0.97). Belief in miracles (aOR 0.30, CI 0.10, 0.96) and higher intrinsic religiosity (aOR 0.70, CI 0.53, 0.93) were associated with lower hospice utilization. CONCLUSIONS: Few religious variables are associated with end of life preferences or treatment. Belief in miracles and intrinsic religiosity may affect treatment and should be identified and explored with surrogates by trained chaplains or other clinicians with appropriate training.